Power management control system for computer laboratories - Bulay-Og, Lory Liza D. (Animo Repository, 2018)
A power management control system is designed and proposed in this research that aims to monitor and control the power energy distribution on computer laboratories and classrooms based on the time of the day and the number of students inside the room. A cheap CPLD board is used as a control mechanism which minimizes power energy wastage that results in minimizing the electrical consumption of computer laboratories and classrooms. Two adjacent computer laboratories were used to as testbed in controlling the electrical power distribution on each room and the air-conditioning system based on the time of the day and the number of people inside the laboratories. Initial results show that a 7.70% reduction in the power consumption is achieved by the proposed system. Finally, a database system for class schedules is used to control power energy distribution on computer laboratories. © 2018 Universiti Teknikal Malaysia Melaka. All rights rerserved.